2021
DOI: 10.3390/su13147671
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Trust and Risk in Citizens’ E-Government Services Adoption: A Perspective of the Extended UTAUT Model

Abstract: This research particularly aims to investigate how trust and perceived risk influence citizens’ e-government adoption. The findings of the study reveal that citizens’ trust of the government (TOG) and trust of the internet (TOI) positively affect citizens’ e-government adoption (EGA); perceived risk (PR) is negatively associated with citizens’ EGA. Interestingly, this study also demonstrates the negative moderating effect of PR on the relationship between TOG and EGA, TOI and EGA. The results also indicate tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
62
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(70 citation statements)
references
References 43 publications
6
62
0
2
Order By: Relevance
“…Researchers in Taiwan also found that mobile-phone navigation is widely accepted as compared to web browser because of the user-friendliness design of mobile phone's interface [36]. A study on citizens' e-government services adoption was conducted recently by using extended UTAUT model [37]. Li observed that most of the constructs of UTAUT, including EE, exhibited positive effects on the services adoption [37].…”
Section: Effort Expectancymentioning
confidence: 99%
See 2 more Smart Citations
“…Researchers in Taiwan also found that mobile-phone navigation is widely accepted as compared to web browser because of the user-friendliness design of mobile phone's interface [36]. A study on citizens' e-government services adoption was conducted recently by using extended UTAUT model [37]. Li observed that most of the constructs of UTAUT, including EE, exhibited positive effects on the services adoption [37].…”
Section: Effort Expectancymentioning
confidence: 99%
“…A study on citizens' e-government services adoption was conducted recently by using extended UTAUT model [37]. Li observed that most of the constructs of UTAUT, including EE, exhibited positive effects on the services adoption [37].…”
Section: Effort Expectancymentioning
confidence: 99%
See 1 more Smart Citation
“…Tangible (SQT) was measured by 4 items, SQP was measured by 4 items, while SQA and SQE were each measured by 3 items derived from [ 3 ]. Effort Expectancy (EE) was measured by 4 derived from [ 57 ]. The constructs PE, SI, and FC were measured by 3 items each derived from [ 57 ].…”
Section: Survey Design/methodsmentioning
confidence: 99%
“…Effort Expectancy (EE) was measured by 4 derived from [ 57 ]. The constructs PE, SI, and FC were measured by 3 items each derived from [ 57 ]. Table A1 summarizes the constructs and their measures for each original source.…”
Section: Survey Design/methodsmentioning
confidence: 99%